The San Bernardino, California, Terror Attack: Two Emergency Departments’ Response - Lee, Carol (West J Emerg Med, 2016)
On December 2, 2015, a terror attack in the city of San Bernardino, California killed 14 Americans and injured 22 in the deadliest attack on U.S. soil since September 11, 2001. Although emergency personnel and law enforcement officials frequently deal with multi-casualty incidents (MCIs), what occurred that day required an unprecedented response. Most of the severely injured victims were transported to either Loma Linda University Medical Center (LLUMC) or Arrowhead Regional Medical Center (ARMC). These two hospitals operate two designated trauma centers in the region and played crucial roles during the massive response that followed this attack. In an effort to shed a light on our response to others, we provide an account of how these two teaching hospitals prepared for and coordinated the medical care of these victims. In general, both centers were able to quickly mobilize large number of staff and resources. Prior disaster drills proved to be invaluable. Both centers witnessed excellent teamwork and coordination involving first responders, law enforcement, administration, and medical personnel from multiple specialty services. Those of us working that day felt safe and protected. Although we did identify areas we could have improved upon, including patchy communication and crowd-control, they were minor in nature and did not affect patient care. MCIs pose major challenges to emergency departments and trauma centers across the country. Responding to such incidents requires an ever-evolving approach as no two incidents will present exactly alike. It is our hope that this article will foster discussion and lead to improvements in management of future MCIs.